The Effectiveness of Murf AI in Canva on Students' English Listening Comprehension - Paquitta Anggreani Iswanto (Journal of Technology and System Information, 2026)
Listening  comprehension  is  one  of  the  essential  skills  in  English  learning,  yet  many  junior  high  school  students  still  face  difficulties  in  understanding  spoken  texts.  This  study  aims  to  examine  the  effectiveness  of  using  Murf  AI  in  Canva  to  improve  students’  listening  comprehension  skills.  A  quasi-experimental  design  was  employed  involving  two  groups:  Class  8B  as  the  experimental  group  and  Class  8A  as  the  control  group.  The  experimental  group  was  taught  using  Murf  AI  in  Canva,  while  the  control  group  received  conventional  instruction.  Data  were  collected  through  pre-tests  and  post-tests  and analyzed using the Mann–Whitney U test and effect size calculation. The  results  revealed  a  statistically  significant  difference  between  the  two  groups,  with  the  experimental  group  achieving  higher  mean  scores  than  the  control  group.  However,  the  effect  size  was  found  to  be  small,  indicating  a  limited magnitude of improvement. In  conclusion,  the  use  of  Murf  AI  in  Canva  has  a  significant  effect  on  students’  listening  comprehension  skills.  Although  the  impact  is  relatively  small,  this  tool  can  be  considered  an  alternative  strategy  to  support  listening  instruction  in